2018
DOI: 10.1155/2018/5389829
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Assessment of Rebar Corrosion in Concrete Slab Using Ground Penetrating Radar (GPR)

Abstract: Corrosion of steel reinforcement is a major cause of structural damage that requires repair or replacement. Early detection of steel corrosion can limit the extent of necessary repairs or replacements and costs associated with the rehabilitation works. The ground penetrating radar (GPR) method has been found to be a useful method for evaluating reinforcement corrosion in existing concrete structures. In this paper, GPR was utilized to assess corrosion of steel reinforcement in a concrete slab. A technique for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 47 publications
0
16
0
1
Order By: Relevance
“…The analysis was based on the evaluation of B-scans and A-scans, detecting changes on the amplitude of the reflected signal and changes in the blurring of the images. Previous reported works (e.g., [15,17,22]) have shown that corrosion could be identified both in B-scans due to blurred images and in A-scans due to changes in the amplitude. In those cases, the change in the intensity was related to the chemical action of chlorides in the concrete as consequence of corrosion rebar.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The analysis was based on the evaluation of B-scans and A-scans, detecting changes on the amplitude of the reflected signal and changes in the blurring of the images. Previous reported works (e.g., [15,17,22]) have shown that corrosion could be identified both in B-scans due to blurred images and in A-scans due to changes in the amplitude. In those cases, the change in the intensity was related to the chemical action of chlorides in the concrete as consequence of corrosion rebar.…”
Section: Discussionmentioning
confidence: 93%
“…This non-destructive testing (NDT) technique is highly efficient in the detection of metallic objects embedded in concrete or other non-conductive materials because of the high reflectivity of metals and the contrast between the electromagnetic properties of metals and concrete [12][13][14]. In the last decade, several tests using qualitative and comparative analyses have demonstrated clear changes in the radar signal associated with corroded elements [15][16][17][18][19][20]. Those qualitative results confirm this method as a useful tool in corrosion detection, as it presents several advantages over other methods: non-invasive testing, fast data acquisition, and the possibility of survey large areas.…”
mentioning
confidence: 99%
“…The increase in wave amplitude with corrosion progress is also revealed in [21,22]. On the contrary, lower amplitude in corrosion process, resulting from increased chloride content and presence of corrosion products, is reported in [11]. It seems that in this paper the influence of corrosion products is not clearly distinguished from the effect of chlorides in wave reflection and, consequently, the results can only be attributed to the concurrent action of both effects.…”
Section: Effect Of Reinforcement Corrosion On Gpr Datamentioning
confidence: 51%
“…Previous research [1,7,[10][11][12]17] has revealed that GPR data can be utilized for the assessment of reinforcement corrosion, as well as for the estimation of moisture and chloride content. The research performed so far shows that changes in travel time, wave amplitudes and frequencies, as derived from A-scans, can reveal deterioration processes in concrete structures, and also locate corroded areas within reinforcement.…”
Section: Condition Assessment Using Gpr Datamentioning
confidence: 99%
See 1 more Smart Citation